Developing a CDS ISIS-based online cataloguing and information retrieval interfaces for use in small libraries - Teh, K.H.; Wong, S.F. (University of Malaya, 1996)
Describes the development of ONLIS, a customised user interface for computerised MARC cataloguing and information retrieval targeted for use in small libraries and information centres. Micro CDS/ISIS Ver. 3.07 software package and its built-in Pascal language were used for the design process and development. The design philosophy centres on the development of a very user-friendly and simple interface, capable of mimicking the sdient features 0/ contemporary commercial library package, yet easy to implement and maintain in a small library environment requiring little or no technical expertise. The system incorporates many new features and comprises two main components, namely (a) data entry and file maintenance and (b) information retrieval. A security system is incorporated into the former environment to ensure data integrity and regulate important file maintenance tasks. While the system is ready for immediate implementation in libraries, modifications and enhancements are currently undertaken to make it a truly reliable product. Some degree of user training in MARC and cataloguing using AACR2 is necessary to get the maximum benefits from the system.